How is a psychotherapeutic process like a psychedelic drug? Neurocognitive evidence for a novel mechanism of action with Regenerating Images in Memory - Cook, Paul F.; Aagaard, Laurra M.; Krug Avery, Lisa; Long, Nichole; Alford, Allen; Sandella, Deborah (Frontiers in Psychology, 2025)
ObjectiveNursing students are at risk for traumatic stress, but current treatments have limited benefits. Regenerating Images in Memory (RIM) is a verbal psychotherapeutic approach to help people safely re-experience troubling memories, then integrate them into meaningful life narratives. RIM’s developers propose a mechanism of action based on nonconscious processes like emotional processing and body awareness. Two Minds Theory (TMT) is a health behavior model that suggests coping arises primarily from the speedy and non-conscious Intuitive Mind. This study was designed to test a potential mechanism of action for RIM based on TMT, where the Intuitive Mind suggests solutions that are later integrated into the Narrative Mind.MethodsIn this exploratory, descriptive, mechanistic study with no comparison group, 30 nursing students received RIM during the late COVID-19 pandemic. Participants completed validated symptom questionnaires before and after 1 RIM session lasting 1–2 h. As an exploratory measure, we measured altered states of consciousness using a scale linked to rapid improvement in studies of psychedelic treatments. Sessions were audio-recorded and participants’ brainwaves were monitored using a MUSE S (Gen 1) 5-lead EEG headband with MindMonitor software.ResultsStudents reported pre-post improvements (Cohen’s d = 1.93–2.75) on 4 of 5 questionnaires. Participants reported levels of altered consciousness similar to those in psychedelic drug studies, particularly on an “ineffability” subscale linked to symptom improvement. EEG readings showed a significant shift away from the frontal lobes (associated with the Narrative Mind) and into the temporal lobes (associated with the Intuitive Mind), χ2 = 11.0 × 104, p < 0.001, during the middle stage of RIM. This was followed by frontal and temporal lobe co-activation during the final stage of RIM, a finding that also mirrors psychedelic studies’ finding of increased synchronization across brain areas during treatment.ConclusionReplicating prior pre-post RIM studies, nursing students reported symptom improvement. These changes co-occurred with altered consciousness and increased temporal-lobe brain activity, findings that are consistent with RIM’s proposed mechanism of action based on TMT. Although this uncontrolled trial does not allow conclusions about treatment efficacy, RIM is a brief verbal psychotherapeutic intervention that merits further study.